2015
DOI: 10.1111/cag.12169
|View full text |Cite
|
Sign up to set email alerts
|

Examining the public health implications of drinking water–related behaviours and perceptions: A face‐to‐face exploratory survey of residents in eight coastal communities in British Columbia and Nova Scotia

Abstract: In Canada the quality of drinking water and its availability are a reflection of where one lives. Coastal communities, which are particularly susceptible to boil water advisories, present an understudied opportunity to understand drinking water–related behaviours and perceptions. How public health practitioners determine actions needed to prevent water‐borne illness is a key factor in the public adopting messaging and/or employing behavioural change. This study involved face‐to‐face surveys with residents in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
(58 reference statements)
3
14
0
Order By: Relevance
“…According to the previous studies, highly educated individuals have less preference for consumption of bottled water. Possibly, this echoes the fact that educated individuals have better access to scientific information related to drinking water quality (14, 18, 19). Scientific enquiries revealed that despite marketing bottled water as a safer alternative to tap water, in the regions with poor water quality, there were concerns about potential chemical leaks from bottles during a long storage period, particularly under unfavorable conditions (high temperature, sunlight, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, highly educated individuals have less preference for consumption of bottled water. Possibly, this echoes the fact that educated individuals have better access to scientific information related to drinking water quality (14, 18, 19). Scientific enquiries revealed that despite marketing bottled water as a safer alternative to tap water, in the regions with poor water quality, there were concerns about potential chemical leaks from bottles during a long storage period, particularly under unfavorable conditions (high temperature, sunlight, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…While most Canadian citizens have access to safe drinking water, many First Nations communities are forced to treat water sources, or are altogether lacking clean water access. Although non-Indigenous rural communities are also impacted [10], studies have demonstrated that First Nations in Canada are disproportionately affected by poor water quality.…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian study of local public perception of risk to drinking water found that risk was underrated (Castleden, Crooks, and van Meerveld 2015). Local residents to a small extent acknowledged that health issues such as gastro-intestinal problems can be caused by contaminants in the drinking water.…”
Section: Drinking Water Risk Management: State Of the Artmentioning
confidence: 99%